Outcomes of transoral laser microsurgery and transoral robotic surgery in oropharyngeal squamous cell carcinoma. Issue 2 (April 2021) - Sievert, Matti; Goncalves, Miguel; Zbidat, Ali; Traxdorf, Maximilian; Mueller, Sarina K.; Iro, Heinrich; Gostian, Antoniu-Oreste
Abstract: Objective: Transoral robotic surgery (TORS) has evolved to a standard therapy modality for oropharyngeal carcinoma, especially in T1/ T2 tumors involving the base of the tongue due to its advantages compared with open surgery. However, knowledge about its benefits compared with transoral laser microsurgery (TLM) are scarce. This study compares oncological and functional results of TLM or TORS in the treatment of oropharyngeal squamous cell carcinoma (OPSCC). Methods: This retrospective analysis comprises all patients with OPSCC treated with TLM (n = 30) or TORS (n = 24) between April 2003 and May 2018 (follow-up 43 ± 38.3 months). Both treatment groups (TLM and TORS) were comparable in terms of the stage of the disease, prognosis-determining factors, and adjuvant therapy modalities. Results: There were no significant differences regarding to the resection status ( p  = 0.272), the rate of local- ( p =  0.834) and distant- recurrence ( p =  0.416), with a disease-free survival of 86.7 % and 87.5 %, respectively ( p =  0.892). In addition, we could not confirm any differences regarding to operating time ( p =  0.860), intraoperative blood loss ( p =  0.660), inpatient stay ( p =  0.585) and postoperative bleeding rate ( p =  0.245). The frequency of tracheostomy and percutaneous endoscopic gastrostomy between both groups is comparable, with a longer duration of tube feeding in patients who have received TLM ( p =  0.030). Conclusion: In conclusion, TORS allows for similar oncological outcomes compared with TLM at comparable perioperative risks. The postoperative swallowing function may benefit from TORS.